PENERAPAN PENDEKATAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIK - astri elpiani; Asep Bagas (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
This study aims to determine the ability of mathematical creative thinking students who learn using the Problem Based Learning approach. The population in this study were students of SMP 1 Jatisari class VIII A in Sukamaju Village which consisted of 18 students and 12 female students. This study was a quasi-experimental study using the results of a trial test pretest-posttest experimental control group. The instrument used in this study is a test to measure mathematical creative thinking skills in the form of 5 questions. Then the score data of students' mathematical creative thinking ability were analyzed statistically by using a difference test of two average values from the results of the pretest-posttest. The results showed that students' creative mathematical thinking ability using the Problem Based Learning approach was different from the results of the pretest-posttest. Besides that students also showed positive perceptions of problem-based learning and there were good results on mathematical creative thinking skills.